Double step screening using endogenous marker improves relative gene targeting efficiency in Arabidopsis - Yiqiu Cheng; Lei Zhang; Yongping Ke; Xiaofei Dang; Daisuke Miki (Scientific Reports)
Abstract Gene targeting (GT) is a powerful tool for manipulating endogenous genomic sequences as intended. However, its efficiency is rather low, especially in seed plants. Numerous attempts have been made to improve the efficiency of GT via the CRISPR/Cas systems in plants, but these have not been sufficiently effective to be used routinely by everyone. Here, we report a surrogate screening method that improves the relative efficiency of CRISPR/Cas9-mediated GT in Arabidopsis. Our findings indicate that simultaneous mutagenesis of the endogenous MAR1 gene, which results in kanamycin resistance, can be employed to efficiently screen for precise and heritable GT events at multiple endogenous sites in the Arabidopsis genome. In this study, we demonstrate that a double-step screening strategy can achieve up to a four-fold increase in the efficiency of GT in Arabidopsis. The principle of this surrogate system has the potential to be widely applied.